Cushing syndrome secondary to a medullary thyroid carcinoma: Report of a case and review of the literature (2014)
We report the case of a 29-year old female who was evaluated because of a thyroid tumor. The initial pathological classification was an insular thyroid carcinoma. There was strong involvement in the neck, mediastinum and lungs. Three years after receiving specific therapy for her thyroid neoplasia, she developed a Cushing syndrome and liver lesions suggestive of metastases from the primary tumor. A review of the previous pathological material revealed a medullary thyroid carcinoma producing ACTH, instead of the insular carcinoma. Based on this case a review of the literature is presented.